Effect of Noise Management in Interventional Radiology Suites on Patients Undergoing Transarterial Chemoembolization: A Retrospective Study - Yong Lu; Lingyu Ma; Zhuo Chen; Hui Qi; Zhaotian Gu; Lei Wu; Benfang Fan (Noise and Health)
Objective: This study aims to evaluate the effect of noise management in interventional radiology suites on patients undergoing transarterial chemoembolization (TACE). Methods: A retrospective cohort study design was employed. The study included a total of 141 patients with hepatocellular carcinoma who underwent TACE surgery in interventional radiology suite of the First People’s Hospital of Nantong from January 2022 to December 2022. The patients were divided into an observation group (received noise management, n = 70) and a control group (did not receive noise management, n = 71) on the basis of whether they received noise management. Patient demographics and surgical data were collected, and heart rate, blood pressure, and anxiety levels were assessed before, during and after surgery. Satisfaction and the incidence of adverse reactions were also documented. Results: No significant differences were found in general characteristics. The comparison between the observation and control groups revealed statistically significant differences in noise levels (P < 0.001). Additionally, anxiety levels significantly differed between the two groups (P = 0.040) as well as across different time points (P < 0.001). However, no significant difference was found in the occurrence of adverse events between groups (P = 0.772). Furthermore, patient satisfaction was significantly higher in the observation group than that in the control group (P < 0.001). Although no significant differences were found in heart rate and systolic blood pressure between groups (P > 0.05), and a significant main effect of time was observed for both variables (P < 0.001). Conclusion: Noise management in the interventional radiology suite effectively alleviates intraoperative anxiety among patients with TACE and improves treatment satisfaction but has no significant effect on physiological changes and the incidence of adverse events.